Analisis Efektivitas Dan Efisiensi Realisasi Anggaran Belanja Pada Dinas Pendidikan Kota Surakarta Tahun 2019-2022 - Anita Nurhidayah; Nadia Putri Bremara; Maya Widyana Dewi (Jurnal Akuntansi dan Pajak, 2024)
This research was conducted with the aim of analyzing the budget reports at the Surakarta City Education Office to see whether they have reached the level of effectiveness and efficiency. This research was conducted at the Surakarta City Education Office with data samples taken starting in 2019-2022. This type of research is qualitative research. The data used are primary data and secondary data. Data collection methods use library research and documentation. The data analysis method uses efficiency level calculations and effectiveness level calculations. The research results obtained in this study are based on the level of effectiveness, namely that the 2019, 2021 and 2022 budgets were quite effective, while the 2020 budget was not effective. Based on the level of efficiency obtained in 2019 and 2020, the budget used was very efficient, while in 2021 and 2022 the budget used was quite efficient.